The Impact of English Proficiency on the Academic Success of English Literature Students: An Analysis Using Structural Equation Modeling (SEM) - Elvira, Melly; Sainuddin, Syamsir; Aisyah, Sri; Rasyid, Muhammad Nur Akbar (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3172, 2024)
This study aims to investigate the relationship between English proficiency (writing, speaking, listening, reading) and academic success among English Literature students at UIN Alauddin Makassar. Structural Equation Modelling (SEM) was used to analyse data collected from 124 respondents through a questionnaire measuring their proficiency in English and self-assessment of their abilities. The analysis revealed that speaking and reading skills significantly influence academic success, while writing and listening skills do not contribute significantly. The implications suggest the need for developing more focused and effective learning strategies to enhance students' speaking and reading skills. These findings are expected to contribute to curriculum improvement and instructional strategies in academic environments to enhance academic achievement among English Literature students.